2019
DOI: 10.7567/1347-4065/ab36f6
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of dielectric measurement using a probe-backside reflection method up to 300 GHz

Abstract: This study demonstrates a novel low-loss dielectric measurement technique that utilizes reflections at the backside of a probe in the millimeterwave frequency range up to 300 GHz. The accuracy of measurement was investigated by evaluating the measurement uncertainty contributors individually. Further, the dielectric dispersion of alumina was calculated from a phonon model. The evaluated dielectric constant and dielectric loss tangent corresponded with values in the accuracy range generated by the phonon model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is noted that the PBR method is insensitive to differences in characteristic impedance (Z c ) from 50 Ω. 18) Though the S 21 trace becomes more rippling when Z c is far from the system impedance, which is 50 Ω, the impact of the rippled trace can be reduced by the compensation technique discussed in Ref. 20.…”
Section: Characteristic Impedancementioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the PBR method is insensitive to differences in characteristic impedance (Z c ) from 50 Ω. 18) Though the S 21 trace becomes more rippling when Z c is far from the system impedance, which is 50 Ω, the impact of the rippled trace can be reduced by the compensation technique discussed in Ref. 20.…”
Section: Characteristic Impedancementioning
confidence: 99%
“…On the other hand, the PBR method generates pseudoresonance by controlling the position of the hf probe in precision on a coplanar waveguide (CPW). [16][17][18][19][20][21] The PBR method can suppress the dimensional error of a resonator because it is determined by the accuracy of the probe position, which is generally smaller than the manufacturing error of the resonator. In addition, the author developed an original measurement technique for minimizing variation in probe position to less than 1 μm.…”
Section: Introductionmentioning
confidence: 99%
“…A fully automatic probe station was constructed to apply the RSD technique. The details of the probe station have been published previously [22][23][24][25][26]. The measurements were conducted in two frequency bands, which ranged from 1 GHz to 110 GHz (100 GHz band) and from 220 GHz to 325 GHz (300 GHz band).…”
Section: A Measuring Instrumentsmentioning
confidence: 99%
“…The developed probing system significantly improved the reproducibility of on-wafer measurements. The alignment technique has demonstrated that in the frequency range up to 340 GHz [24][25][26]. The RSD technique is expected to solve three of the abovementioned problems in the long-term stability test of on-wafer measurements because the contact position is defined at the actual contact point, which is not at the apex of the probe silhouette.…”
Section: Introductionmentioning
confidence: 99%
“…17 The complex permittivity in the gigahertz range is often measured using an electrical resonance technique that is applicable below 300 GHz. 18 By contrast, the complex permittivity in the terahertz range is usually estimated via infrared reflectance and transmittance 19 ; however, glasses are often opaque in the terahertz range, which prevents the transmittance from being accurately determined. Furthermore, the complex permittivity of amorphous materials has rarely been estimated by Kramers-Kronig transformation.…”
Section: Introductionmentioning
confidence: 99%